Penerapan Sosialisasi Digital Marketing Guna Meningkatkan Penjualan di Kelurahan Bendogerit - Khairani Liesvarastantra Tsani; Acep Samsudin (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Technology has developed rapidly in the age of scientific progress. This is unavoidable because technology can provide positive benefits for developing product innovations. With the existence of technology, humans can use it as access to search for extensive information via the internet. Socialization of Digital Marketing and Creating a Marketplace for MSME Players